PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI, LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP KEPUASAN KERJA KARYAWAN (STUDI PADA KARYAWAN GENERASI Z DI DKI JAKARTA) - Almira Talitha Zuleiha; Antyo Pracoyo; Enny Haryanti; Subarjo Joyosumarto (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to evaluate the level of job satisfaction among Generation Z employees in the Jakarta Special Capital Region (DKI Jakarta). The analysis focuses on four variables considered to have potential influence on job satisfaction: leadership style, compensation, work environment, and organizational culture. These four aspects are treated as independent variables, while job satisfaction serves as the dependent variable whose relationship is examined. A quantitative approach was employed to process the collected data, utilizing the Structural Equation Modelling (SEM) method, specifically the Partial Least Squares (PLS) technique. Data analysis was conducted with the assistance of SmartPLS software. Primary data were obtained through online questionnaires distributed via Google Forms, targeting respondents categorized as Generation Z employees currently working in Jakarta. The findings reveal that leadership style and work environment have a significant and positive impact on job satisfaction. This suggests that effective leadership and a supportive work setting can enhance employees’ overall satisfaction. On the other hand, while compensation and organizational culture also show a positive relationship with job satisfaction, their influence is not statistically significant. In other words, these two variables do not exert a strong enough effect to explain the variations in job satisfaction among Generation Z employees within the scope of this study.